Health Financing System Assessment : Papua New Guinea - World Bank Group (World Bank, Washington, DC, 2018)
The health sector of Papua New Guinea (PNG) has seen significant positive developments in recent years. Key indicators of health access and quality have, however, barely improved or have even declined (for example, maternal and child health) from 2006 to 2015. In 2016, PNG entered the accelerated transition phase from the vaccine alliance (Gavi) support. During this time, the government will be expected to increase its share of co-financing for vaccines, while Gavi gradually decreases their contribution. The government is simultaneously moving towards universal health coverage (UHC), along with many other developing countries, and has recently established fee free primary health care and subsidized secondary care. Given this backdrop, the health financing system assessment (HFSA), which evaluates the financing system and institutional sustainability, comes at an opportune time. The report begins by providing a comprehensive background, including an overview of PNG’s economic situation, health demographics, health financing, human resources for health and the health system. It then analyses two areas critical to sustainable health financing: (i) PNG expenditure, with a focus on levels and sources of health expenditure, as well as resource allocation; and (ii) PNG reliance on donor resources, in particular, the global fund to fight aids, tuberculosis, and malaria (GFATM) and Gavi.